185k views
5 votes
Solve for x.
3x – 4(4x – 8) = 3(- 8x - 1)

User Userfuser
by
5.5k points

2 Answers

4 votes
3x - 4(4x - 8) = 3(-8x - 1)
3x - 16x + 32 = -24x - 3
3x - 16x + 24x = -3 - 32
11x = -35
X = - 35/11

User Fahd Arafat
by
5.7k points
4 votes

Answer:

x=-35/11

Explanation:

3x-4(4x-8)=3(-8x-1)

3x-16x+32=3(-8x-1)

-13x+32=-24x-3

-32 -32

-13x=-24x-35

+24x +24x

11x=-35

/11 /11

x=-35/11

User Suketu Bhuta
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.